Corak pengambilan makanan di kalangan kanak-kanak pra sekolah yang mengalami masalah pendengaran jenis sensorineural - Abdul Talib, Ruzita; Umat, Cila; Ismail, Noraidah; Safii, Nik Shanita (Fakulti Sains Kesihatan Bersekutu, Universiti Kebangsaan Malaysia, 1999)
The study was aimed to determine the pattern of daily food intake among the Malaysian pre-school children with sensorineural hearing impairment. Thirty-one pre-school children with sensorineural hearing impairment aged 3-6 years who attended the Audiology & Speech Clinic, UKM were chosen as study subject and the control group (n=5) were normal hearing children from the same age group. The subjects’ hearing threshold levels and type of hearing loss were determined by means of either play audiometry and/or auditory brainstem responses (ABR). Subjects in the control group were screened using play audiometry. Tympanometry was performed on all subjects to ascertain functioning middle ear, thus excluding those with conductive and/or mixed hearing loss. Daily food intake was evaluated using a 24-hour dietary recall and food frequency questionnaire. The results showed that the mean energy intake of the pre-school children with sensorineural hearing impairment and the control group was lower than the Malaysian RDA. The mean intake of protein, vitamin A, vitamin B, vitamin C and iron of the both groups were found to be above the Malaysian RDA. However, their mean intake of calcium and fiber were lower than the Malaysian RDA. These results suggest that there is a need for improving the quality of the dietary intake of the pre-school children with sensorineural hearing impairment as well as nutrition education on the healthy eating among their parents